Transformasi Sosial melalui Pendidikan dan Pengabdian Masyarakat Berbasis Nilai Lokal - Fhadil, Shahibul; Rian Noveri; Gusmaneli (CV. ITTC INDONESIA, 2024)
This study explores the critical role of local values in education and their impact on social transformation. It emphasizes the integration of local wisdom into educational curricula to enhance students' cultural identity and social awareness. By incorporating local values, education can foster a sense of belonging and community, ultimately leading to a more cohesive society. The research highlights various strategies for implementing local wisdom in educational practices, particularly in Indonesia, where diverse cultures coexist. These strategies include collaborative learning, community engagement, and the use of culturally relevant materials that resonate with students' backgrounds. The findings suggest that a curriculum enriched with local values not only improves academic performance but also nurtures character development among students. Furthermore, this approach encourages students to appreciate their heritage and promotes respect for diversity, which is essential in today’s globalized world. Ultimately, integrating local wisdom into education can empower students to become active and responsible citizens in their communities.